DIABETIC MACULAR ISCHEMIA: Correlation of Retinal Vasculature Changes by Optical Coherence Tomography Angiography and Functional Deficit. Issue 11 (November 2020) - Tsai, Andrew S. H.; Gan, Alfred T. L.; Ting, Daniel S. W.; Wong, Chee Wai; Teo, Kelvin Y. C.; Tan, Anna C. S.; Lee, Shu Yen; Wong, Tien Yin; Tan, Gavin S. W.; Gemmy Cheung, Chui Ming
Abstract : Purpose: To examine the relationship between macular microvasculature parameters and functional changes in persons with diabetic retinopathy (DR). Methods: Cross-sectional study of 76 eyes with varying levels of DR. Optical coherence tomography angiography (OCTA) quantified superficial and deep perifoveal vessel densities and foveal avascular zone areas. Retinal sensitivity was measured using microperimetry. Optical coherence tomography angiography parameters and retinal sensitivity were correlated. Results: Deep perifoveal vessel density decreased with increasing severity of DR (adjusted mean 51.93 vs. 49.89 vs. 47.96, P -trend = 0.005). Superficial and deep foveal avascular zone area increased with increasing DR severity (adjusted mean: 235.0 µ m 2 vs. 303.4 µ m 2 vs. 400.9 µ m 2, P -trend = 0.003 [superficial]; 333.1 µ m 2 vs. 513.3 µ m 2 vs. 530.2 µ m 2, P -trend = 0.001 [deep]). Retinal sensitivity decreased with increasing DR severity (adjusted mean: 25.12 dB vs. 22.34 dB vs. 20.67 dB, P -trend = 0.003). Retinal sensitivity correlated positively with deep perifoveal vessel density (Pearson's ρ = 0.276, P = 0.020) and inversely with superficial foveal avascular zone area (Pearson's ρ = −0.333, P = 0.010). Conclusion: Alterations in retinal microvasculature can be observed with OCTA with increasing severity of DR. These changes are correlated with reduced retinal sensitivity. Optical coherence tomography angiography is useful to detect and quantify the microvasculature properties of eyes with diabetic macular ischemia. Abstract : Increasing severity of diabetic retinopathy was associated with optical coherence tomography angiography changes in retinal microvasculature, which correlated with retinal sensitivity. Optical coherence tomography angiography was able to detect and quantify the microvasculature properties of eyes with diabetic macular ischemia, and there is potential to measure diabetic macular ischemia progression longitudinally.